Schedule-dependent increased efficiency of pemetrexed-ionizing radiation combination therapy elicits a differential DNA damage response in lung cancer cells. Issue 1 (December 2016) - Dorn, Patrick; Tièche, Colin; Peng, Ren-Wang; Froment, Laurène; Schmid, Ralph; Marti, Thomas
Abstract Background Lung cancer causes the most cancer deaths worldwide, thus there is a urgent need to develop new treatment options. Concurrent chemoradiotherapy has become a common strategy for the treatment of non-resectable solid tumors including non-small cell lung cancer. Pemetrexed is a folic acid antagonist that inhibits the synthesis of precursor nucleotides, whereas ionizing radiation induces DNA damage, the repair of which is dependent on sufficiently high nucleotide levels. In the clinical setting, the pemetrexed-ionizing radiation combination therapy is administered concomitantly. We hypothesized that prolonged pretreatment with pemetrexed could be beneficial, as prior depletion of nucleotide pools could sensitize cancer cells to subsequent irradiation. Methods Non-small cell lung cancer A549 cells were treated with 1 µM pemetrexed for 72 h. In addition, cells were exposed to five gray ionizing radiation either 1, 48 or 71 h after the initiation of the pemetrexed treatment. Cell growth, senescence induction, cell cycle distribution and DNA damage marker accumulation were analysed at different time points during the treatment and the recovery phase. Results Stand-alone treatments of five gray ionizing radiation and 1 µM pemetrexed resulted in an intermediate cell growth inhibition of A549 cells and were therefore applied as the combination regimen. Prolonged pemetrexed pretreatment for 71 h resulted in a significant S-phase accumulation. Irradiation and prolonged pemetrexed pretreatment maximally delayed long term cell growth. Additionally, senescence was augmented and recovery from treatment-induced DNA damage was most prominently delayed by prolonged pemetrexed pretreatment. Conclusions Pretreatment with pemetrexed increases anticancer efficiency of pemetrexed-ionizing radiation combination therapy, which correlates with a persistence of treatment-induced DNA damage. Therefore, this study warrants further investigations to elucidate whether a similar adaptation to the standard treatment regimen could enhance the effectiveness of the non-small cell lung cancer clinical treatment regimen.